2022
DOI: 10.3389/fonc.2022.1008361
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of lipid metabolism reprogramming in head and neck squamous cell carcinoma: An overview

Abstract: Recent studies showed that lipid metabolism reprogramming contributes to tumorigenicity and malignancy by interfering energy production, membrane formation, and signal transduction in cancers. HNSCCs are highly reliant on aerobic glycolysis and glutamine metabolism. However, the mechanisms underlying lipid metabolism reprogramming in HNSCCs remains obscure. The present review summarizes and discusses the “vital” cellular signaling roles of the lipid metabolism reprogramming in HNSCCs. We also address the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…In this context, the upregulation we observed for apolipoproteins (APOs) and fatty acid desaturase (FADS) gene families remarked the role of lipid profiles in HNSCC [ 72 , 73 ]. However, we did not appreciate this for the carbohydrate or glutamine metabolism, as reported in other studies [ 74 ].…”
Section: Discussionmentioning
confidence: 70%
“…In this context, the upregulation we observed for apolipoproteins (APOs) and fatty acid desaturase (FADS) gene families remarked the role of lipid profiles in HNSCC [ 72 , 73 ]. However, we did not appreciate this for the carbohydrate or glutamine metabolism, as reported in other studies [ 74 ].…”
Section: Discussionmentioning
confidence: 70%
“…Circulating tumor cells, using CAMs present on their surface to adhere to the endothelium, exited the vasculature with strong blood ow impact force by extravasation, forming metastases at a distance [48]. It has been found that lipid metabolism was reprogrammed in cancer [49] and also played a crucial role in HNSCC [50]. Lipid metabolism supported the survival, proliferation, invasion, and metastasis of cancer cells by promoting membrane formation, energy production, signal transduction, and even mediating drug resistance [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, it has become increasingly clear that changes in lipid metabolism are commonly associated with advanced, treatment-resistant carcinomas [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. There is extensive evidence for ongoing redesign of lipid metabolism in tumor cells as they progress to more advanced, treatment-resistant carcinoma [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Moreover, hypoxia, commonly experienced by carcinoma cells in vivo and representing a negative clinical prognostic, upregulates fatty acid uptake and storage [ 37 , 38 , 39 ].…”
Section: Context Of “Lipid Metabolism Resistance System” (Lmrs) Hypot...mentioning
confidence: 99%